Protective Role of Tulsi (Ocimum sanctum) on Growth, Hematology, Liver Enzymes (ALP, ALT, and AST), and Immune System Against Lead-Induced Toxicity in Thaila (Catla catla) - Noreen , Ayesha; Akhtar, Amara; Zafar, Amina; Yaseen, Ayesha (Indus Journal of Bioscience Research, 2025)
Aquaculture is the biggest fish production sector that meets the demands of fish globally. Lead (Pb) pollution from various human activities poses a significant threat to aquatic life. The present study explored the adverse effects of lead-based toxicity in Catla catla (C. catla) and the ameliorative role of Ocimum sanctum (O. sanctum) supplementation. There were four treatments in which forty-eight fishes were equally distributed. T0 was the control group fed with a basal diet. T1 was fed with 7 mg/L lead. T2 was fed with O. sanctum (10 g/kg) and T3 was co-treated with lead (7 mg/L) and O. sanctum (10 g/kg). Lead and O. sanctum Group (T₃) showed improved growth (27.05±1.07) as compared to the lead group (21.11±1.38) which indicated that O. sanctum supplementation mitigated some of the adverse effects of lead toxicity. Length gain was maximum in T2 (12.23±0.58) as compared to other groups. RBC count (1.35±0.06), hematocrit (24.14 ±2.62) and hemoglobin (5.12±0.04) decreased in the lead group. WBC count (48.66±0.61) increased in lead-exposed group T1 as compared to other treatments. ALT (32.03 ±1.83), AST (57.16±1.56) and ALP Levels (27.93±4.25) increased in the lead group (T1) indicating significant liver damage due to lead toxicity. The T₃ group showed lower enzyme level ALP (23.58±2.07), ALT (28.26±1.86) and AST (53.34±0.98) compared to other treatments demonstrating the hepatoprotective effect of O. sanctum. Total serum protein (4.20±0.18 g/dL), albumin (2.12±0.10 g/dL) and globulin (2.08±0.08 g/dL) levels were altered in the lead group showing immune system dysfunction due to lead exposure. In contrast the T₃ group showed improved immune parameters with total serum protein (5.1±0.15 g/dL), albumin (1.46±0.17 g/dL) and globulin (2.13±0.26 g/dL), indicating the beneficial effects of O. sanctum supplementation in restoring immune function. Statistical analysis showed that the results are significant (p<0.05).